High-throughput autoantibody screening identifies differentially abundant autoantibodies in autism spectrum disorder - Mesleh, Areej; Ehtewish, Hanan; Lennard, Katie; Abdesselem, Houari B.; Al-Shaban, Fouad; Decock, Julie; Alajez, Nehad M.; Arredouani, Abdelilah; Emara, Mohamed M.; Albagha, Omar; Stanton, Lawrence W.; Abdulla, Sara A.; et al. (Frontiers in Molecular Neuroscience, 2023)
Introduction: Autism spectrum disorder (ASD) is a neurodevelopmental condition characterized by defect in two core domains, social/communication skills and restricted/repetitive behaviors or interests. There is no approved biomarker for ASD diagnosis, and the current diagnostic method is based on the clinical manifestation, which tends to vary vastly between the affected individuals due to the heterogeneous nature of ASD. There are some emerging evidences that support the implication of the immune system in ASD, specifically autoimmunity; however, the role of autoantibodies in ASD children is not yet fully understood.In this study, we screened serum samples from 93 cases with ASD and 28 healthy controls utilizing the high-throughput KoRectly Expressed (KREX) i-Ome protein-array Formatted: Normal, Centered